Desenvolvimento de Engineered Cementitious Composites (ECC) autocicatrizantes com diferentes fibras poliméricas e agentes de cicatrização - Ehrenbring, Hinoel Zamis (Universidade do Vale do Rio dos Sinos, 2020)
This thesis aimed to develop self-healing ECCs with PVA, polypropylene and recycled polyester fibers. As healing agents, silica fume, crystallizing additive and bacterial solution were used. For autonomous agents, three contents (T1, T2 and T3, ascending order) were stipulated for each one. The experimental program was divided into 4 stages, starting with the determination of the equivalent fiber content between the composites. Then, the classification step of the mixtures was carried out to meet the requirements of the ECC class with structural application.
Keywords: Engineered Cementitious Composites; Autocicatrização; Autorregeneração; Fibras poliméricas; Comportamento à tração; Self-healing; Self-recovering; Polymeric fibers; Tensile Behavior; ACCNPQ::Engenharias::Engenharia Civil